Wireless energy harvesting relaying networks under imperfect CSI: throughput analysis - Dinh , Viet Hoa; Nguyen, Thai Anh; Do, Dinh Thuan (Journal of Technical Education Science, 2017)
The purpose of this research aims to investigate an amplify-and-forward-based (AF) energy harvesting (EH) system with imperfect channel state information (CSI), where two-end-nodes and one relay are operated in half-duplex mode. Power splitting-based relaying (PSR) protocol is used to transmit information from source to destination by the energy harvesting enabled relay. The authors propose that the initial power contained in the battery is used to run the relay. After that, to transmit signal the relay has to harvest energy from the attained RF signals. The exact integral and approximate closed-form expressions for the outage probability and throughput of this system have been derived. The validity of analytical results is verified by Monte Carlo simulations.